Kegiatan Pengabdian Masyarakat dalam Rangka Peningkatan Pemahaman Masyarakat Tentang Penyakit Perlemakan Hati dan Deteksi Dini Penyakit Liver - Shirly Gunawan; Alicia Sarjuwita; Vini Claudya Agustine Rajagukguk; Yohanes Firmansyah (Pusat Riset dan Inovasi Nasional, 2023)
Non-alcoholic fatty liver disease has become a health problem increasing worldwide. This disease is characterized by excessive fat accumulation in the liver cells unrelated to alcohol consumption. Education and risk factor detection are essential in identifying and preventing the development of this disease. This community service involved 52 respondents at Kalam Kudus II Jakarta High School in May 2023. All participants participated in a series of activities starting from community counseling, disease detection, and education. The results of the medical examination revealed that there were 2 (3.8%) respondents who had increased serum glutamic oxaloacetic transaminase (SGOT)/ serum glutamic pyruvic transaminase (SGPT) levels and 6 (11.5%) had hypercholesterolemia. Education about fatty liver disease can increase public awareness of this condition and promote a healthy lifestyle and good eating habits. Detection of risk factors through laboratory tests such as SGOT, SGPT, bilirubin, and cholesterol is also important in early identification of this disease. In effective fatty liver disease management, it is important to increase awareness of counseling and risk factor detection. Collaborative efforts between medical personnel, health educators, and communities can help reduce the burden of this disease and improve the quality of life of affected individuals.